Indywidualizacja źródeł ryzyka systemowego w krajach europejskich - Karkowska, Renata (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
While contemporary systemic risk takes many forms, usually all kinds of wellknown risks overlap in time and space. Considering leverage undertaken by banksas a potential source of systemic risk, the author attempts to discover the factorsintensifying this phenomenon. The article presents the results of a study on datafrom individual banks in 31 European states for the period 2000–2010. The primaryobjective of this study is to verify the diversification of sources of systemicrisk in the banking sectors of developing and developed countries. Evidence ofheterogeneity of systematic risk’s determinants in European countries is provided.